The phytogeography of Southern Mistbelt Forests of the Eastern Cape, South Africa - Matiwane, Aviwe (Rhodes University, Faculty of Science, Botany Department, 2016)
In the Eastern Cape, a moisture gradient (from west to east) exists along the Escarpment where patches of Southern Mistbelt Forests (SMF) occur. There is a notable profusion of plants in these forests, but the factors that drive plant species composition and abundance in these patches is poorly understood and such knowledge is critical if we are to address or mitigate the problems imposed by global change. Many of our ideas on plant community assembly are based on the premise that species differ in their environmental requirements for successful regeneration, especially when young. The aims of this study were to document the floristic diversity of poorly known patches of Southern Mistbelt Forests in the Eastern Cape and identify the environmental factors that influence plant community composition in these forest patches. Twenty six forest patches across the Eastern Cape were sampled. In each forest 400m2 circular plots were constructed. The diameter at breast height and stem counts for the tree species was taken and the % cover of the herbaceous species was recorded. General collections were also made to supplement the plot data in order to obtain a comprehensive flora for each forest patch. All sampling was done during the summer season of 2013 and 2014. Using plot data, Hierarchal Cluster Analysis and Multidimensional Scaling Analysis were done to compare similarities between patches. Plots from the same forest patch clustered which indicated that the species composition in each forest patch was unique. However, this pattern went down when only tree species were considered. Plant diversity also varied between patches; with those located in the east being generally more diverse than those in the west are. Clustering patterns in fragmented communities and differences in species diversity indicate evidence of species "nestedness" . Analysis of nestedness indicated that these forest patches were significantly nested. To identify which environmental variables might be correlated with both species diversity and nestedness, twelve environmental variables was selected for analysis using Canonical Correspondence Analysis and Principal Component Analysis. Results show that Mean Annual Precipitation, Mean Annual Potential Evapotranspiration, and percentage of Organic Matter of the soil were most strongly correlated with the patterns of diversity observed in these forest patches. Regression analysis indicated that Mean Annual Precipitation accounted for most of the variation in species diversity, especially for the herbaceous species. The herbaceous species thus show a greater sensitivity to "climate filtering" as a consequence of rainfall gradients. With the implementation of suitable monitoring programs, changes in abundance or even local extinction of these species can act as an early warning indicator of the possible long-term effects of climate change on forest communities.
Keywords: Uncatalogued